Gem‐Difluorocarbadisaccharides: Restoring the exo‐Anomeric Effect1. (15th July 2014) - Xu, Bixue; Unione, Luca; Sardinha, Joao; Wu, Shaoping; Ethève‐Quelquejeu, Mélanie; Pilar Rauter, Amelia; Blériot, Yves; Zhang, Yongmin; Martín‐Santamaría, Sonsoles; Díaz, Dolores; Jiménez‐Barbero, Jesus; Sollogoub, Matthieu
Abstract Molecular mimicry is an essential part of the development of drugs and molecular probes. In the chemical glycobiology field, although many glycomimetics have been developed in the past years, it has been considered that many failures in their use are related to the lack of the anomeric effects in these analogues. Additionally, the origin of the anomeric effects is still the subject of virulent scientific debates. Herein, by combining chemical synthesis, NMR methods, and theoretical calculations, we show that it is possible to restore the anomeric effect for an acetal when replacing one of the oxygen atoms by a CF2 group. This result provides key findings in chemical sciences. On the one hand, it strongly suggests the key relevance of the stereoelectronic component of the anomeric effect. On the other hand, the CF2 analogue adopts the natural glycoside conformation, which might provide new avenues for sugar‐based drug design.